The practice of counselling in primary care - Bor, Robert; McCann, Damian; Sage eBooks (London : SAGE, 1999)
Wide-ranging yet cohesive, this book addresses the unique issues faced by counsellors working in primary care settings including maximising therapeutic contact whilst using time-limited techniques, referrals and the management of patient flow.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Mental health counseling; Primary care (Medicine); Electronic books